What predicts the Militant Extremist Mindset? An investigation into the relationship between violent extremism, and personality, moral disengagement, and linguistic markers - Janjua, Zara (2021)
This thesis investigates the psychological underpinnings of the Militant Extremist Mindset (MEM). The MEM includes three core components: Pro- violence, Vile World, and Divine Power. The thesis includes six chapters: a general introduction, a systematic review, two quantitative research studies, a psychometric critique, and a general discussion. The systematic review explored the relationship between violent extremism and the Dark Triad. Findings suggested that, currently, narcissism may be the most influential of the dark traits in the process of radicalisation and extremism. However, there were limited studies included in the systematic review, indicating a need for further research. The first quantitative research study investigated personality traits, and moral disengagement as predictors of the MEM and its three subscales. Hierarchical regression analyses found that Honesty- Humility, and moral disengagement predicted total MEM and the Pro-violence subscale. Openness and age predicted the Divine Power subscale. The second quantitative research study investigated linguistic categories as predictors of the MEM. The results found that the negative emotions, and anger categories correlated with both total MEM and the Divine Power subscale; third person plural pronouns correlated with the Pro-violence subscale, and first-person plural pronouns correlated with the Vile World subscale. Linear regressions found that third person plural pronouns predicted the Pro-violence subscale. Limitations and implications are discussed in both research studies. The psychometric critique discusses and critiques The Violent Extremist Risk Assessment 2 Revised in terms of its psychometric properties and its applicability to forensic practice. Whilst studies relating to this demonstrate promising findings, limitations indicate a need for further independent studies on the tool to test its reliability and validity. The final chapter summarises the key findings across the thesis, the limitations of the methods used, and implications of the findings for the field of violent extremism.